Transcriptomic and Functional Screens Reveal MicroRNAs That Modulate Prostate Cancer Metastasis - Rao, Srinivasa R.; Howarth, Alison; Kratschmer, Patrick; Snaith, Ann E.; Yapp, Clarence; Ebner, Daniel; Hamdy, Freddie C.; Edwards, Claire M. (Frontiers in Oncology, 2020)
Identifying new mechanisms that underlie the complex process of metastasis is vital to combat this fatal step in prostate cancer (PCa) progression. Small non-coding RNAs are emerging as important regulators of tumour cell biology. Here we take an integrative approach to elucidate the contribution of microRNAs to metastatic progression, combining transcriptomic analysis with functional screens for migration and morphology. We developed high-content microscopy, high-throughput functional screens for migration and morphology in PCa cells using a microRNA library. RNA-Seq analysis of paired epithelial and mesenchymal PCa cells identified differential expression of 200 microRNAs. Data integration identified four microRNAs that inhibited migration, induced an epithelial-like morphology and were increased in epithelial PCa cells. An overrepresentation of the AAGUGC seed sequence was detected in all three datasets. The AAGUGC seed sequence, present in 4 microRNA families, was significantly overrepresented in all three datasets. Analysis of published datasets of patients with PCa identified microRNAs of clinical relevance. The integration of high-throughput functional and expression analyses identifies microRNAs with clinical significance that modulate metastatic behaviour in PCa.